Development and Application of the Life Roles Inventory-Values Scale - Loo, Robert; Thorpe, Karran (Canadian Journal of Counselling and Psychotherapy, 2007)
One major result of the Work Importance Study (WIS), started in 1979 by an international consortium of psycholgists under Donald E. Supers' guidance, was the Values Scale, which tapped work and life values. The scale was later revised as part of a Canadian project and renamed the Life Roles Inventory-Values Scale (LRI-VS: MacNab, Fitzsimmons, & Casserly, 1987). The present study used a sample of 202 management and nursing undergraduates to provide a psychometric evaluation of the LRI-VS. Overall, the results from the internal-consistency reliability analyses, factor analyses at the item, value, and component levels, and gender analyses, provided qualified support for the scale. In spite of some psychometric limitations, the usefulness of the LRI-VS as a tool for self-discovery, educational, and career counselling receives qualified support. Further refinement is recommended for the scale.